Bioviabilitas Hidroksiapatit Ekstrak Cangkang Kerang Darah (Anadara granosa) Terhadap Sel Punca Mesenkimal Sebagai Bahan Graft Tulang - Arlita Dewi Nastiti; Widyastuti; Fanny M Laihad (Denta Journal Kedokteran Gigi, 2015)
Background: One of a bone defect fillers is ahydroxyapatite. Hydroxyapatite can be obtained from Anadara granosa shells extract that have high calcium content. The mineral content can be used as a bone filler material for bone grafting. However, the material is not known bioviability to against periodontal tissues so that was needed bioviability testing. This bioviability testing using mesenchymal stem cells as mesenchymal stem cells can differentiate into periodontal tissues. Purpose: To determine bioviability Anadara granosa shell extract on mesenchymal stem cells. Materials and Methods: This study was conducted using post-only control group design. Mesenchymal stem cells in 96 wells were divided into a control group of cells (n=7), media controls (n=7), and treatment (n=7). The treatment group were given various doses of the Anadara granosa shell extract with a concentration 54 mg/ml, 27 mg/ml, 13.5 mg /ml and 6.75 mg/ml. The mesenchymal stem cells were incubated for 24 hours before and after treatment. Once given MTT, the optical density is read by ELISA reader and calculated the percentage of viability. The cell viability data were analyzed with KruskalWallis statistical test, Mann-Whitney. Results: From the results showed that an increase in cell viability to Anadara granosa shell extract. Increased cell viability starting treatment group concentration of 54 mg/ml (23,,67%), 27 mg/ml (57,43%), 13,5 mg/ml (68,87%), 6,75 mg / ml (81,92%). The highest cell viability at concentrations of 6,75 mg/ml (81,92%). Conclusion: Bioviability extract blood clam Anadara granosa shell have the highestconcentration of 6,75 mg/ml and bioviabilitas lowest cell at a concentration of 54 mg/ml.